PENGARUH SPIRITUAL LEADERSHIP, KEPUASAN KERJA DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PABRIK PODO SENENG KEDIRI - Septinia Sari; Kukuh Harianto; Heru Sutapa (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence of spiritual leadership, job satisfaction and self efficacy on the employees performance of Podo Seneng Factory which located in Banjaranyar Village, Kras District, Kediri Regency, East Java 64171. This type of research is quantitative research which includes a hypothesis as an initial research assumption. The sample was 35 respondents using a saturated sampling technique. Technique data analysis is multiple linear regression using SPSS software 25. The results of this research show that spiritual leadership partially has a significant effect on the performance of Podo Seneng Kediri Factory employees. Job satisfaction partially has a significant effect on employee performance Podo Seneng Kediri Factory. Self-efficacy partially has a significant effect on the employees performance of Podo Seneng Kediri Factory. Meanwhile, simultaneously spiritual leadership, job satisfaction and self efficacy have a significant effect on the employees performance of Podo Seneng Kediri Factory. Based on results of the research, the coefficient of determination value is found in R square, 0.943 or 94.3% which means spiritual leadership, job satisfaction and self-efficacyinfluences employee performance variables by 94.3%, the remaining 5.7% performance variables employee performance is influenced by other independent variables that are not mentioned in this research.